From COPD to cancer: indacaterol’s unexpected role in combating NSCLC - Liu, Chenghao; Huang, Jiaqi; Cai, Pengjie; Jiang, Min; Chen, Honglei (Frontiers in Pharmacology, 2025)
BackgroundNon-small cell lung cancer (NSCLC) is one of the most prevalent and deadly malignancies worldwide. In previous studies, indacaterol, a drug used to manage chronic obstructive pulmonary disease, has shown antitumor activity. However, its role in the context of NSCLC remains underexplored. This study aimed to investigate indacaterol’s mechanisms and potential therapeutic effects in lung cancer treatment.MethodsExpression profiles and clinical information from the TCGA database were analyzed to explore the potential impact of the SLC2A1 gene on the progression of NSCLC. The expression levels of the GLUT1 protein, encoded by the SLC2A1 gene, and the MCT4 protein, encoded by the SLC16A3 gene, were analyzed in both lung cancer and normal tissues. Techniques such as cellular thermal shift assay (CETSA), immunofluorescence, and Western blotting were employed to assess the interaction between indacaterol and GLUT1. Immunohistochemistry was used to study the expression of GLUT1 and MCT4 in human tissues. The effects of indacaterol on lung cancer cell lines were observed through wound healing and colony formation assays. Additionally, animal experiments combined with PD-L1 inhibitors were conducted to evaluate the antitumor effects of indacaterol in vitro and in vivo.ResultsAnalysis of TCGA data revealed that GLUT1 has a potential role in promoting NSCLC and may work in concert with MCT4. Indacaterol significantly inhibited the viability of NSCLC cells in a concentration-dependent manner. Molecular modeling and CETSA experiments further indicated that indacaterol may bind to GLUT1 and affect GLUT1 expression. Immunohistochemistry suggested that indacaterol also reduces the expression of MCT4, suggesting its potential to diminish the capacity of tumors to reprogram stromal metabolism. In vitro and in vivo experiments confirmed that the combination of indacaterol with PD-L1 inhibitors synergistically inhibited the proliferation and invasion of NSCLC cells.ConclusionIndacaterol, a potential inhibitor of GLUT1, has significant antitumor effects on NSCLC. Moreover, the combination of indacaterol with immune checkpoint inhibitors may further enhanced the inhibitory effects of indacaterol on NSCLC cells. Our study provides scientific evidence supporting the clinical application of indacaterol as a novel therapeutic strategy for NSCLC treatment.